Analysis of Content Standards in the Perspective of Education Quality Management at Mts Khairul Ummah Jakarta - Wahyudin Wahyudin; Asep Abdul Wadud; Endang Komara (Universitas Muhammadiyah Enrekang, 2023)
Content standards are minimum criteria that cover the scope of material to achieve graduate competency in certain paths, levels and types of education. This study aims to determine: 1) Standards of content in the quality management of education at MTs Khairul Ummah. 2) Analysis of content standards from the perspective of education quality management at MTs Khairul Ummah. This research uses a qualitative research type, with a case study research design at MTs Khairul Ummah. Data collection was carried out by interview, observation, and documentation methods. Data analysis techniques through data collection, data reduction, data presentation and drawing conclusions. Data validation technique, using triangulation of sources and theory. Based on the research data obtained: Analysis of content standards in the perspective of education quality management at MTs Khairul Ummah is carried out by matching data between ideal conditions and existing real conditions starting from planning, implementation, monitoring and supervision, curriculum evaluation which is carried out optimally and is the responsibility of all stakeholders to improve the quality of education at MTs Khairul Ummah.